Perancangan Interior Pusat Informasi dan Rehabilitasi Kelumpuhan Pasca Stroke - Hendra Setiawan; Grace Mulyono (Intra, 2014)
The interior design process aiming to paint the facility for users who need the specific needs. By providing a facility where recovery and also information about stroke. The design will be applied include a health clinic for its users to a host of house rent room stay with attention to aspects of the therapy to the recovery process and also the independence of the activities of the independent